2020
DOI: 10.1371/journal.ppat.1008560
|View full text |Cite|
|
Sign up to set email alerts
|

Repertoire characterization and validation of gB-specific human IgGs directly cloned from humanized mice vaccinated with dendritic cells and protected against HCMV

Abstract: Human cytomegalovirus (HCMV) causes serious complications to immune compromised hosts. Dendritic cells (iDCgB) expressing granulocyte-macrophage colony-stimulating factor, interferon-alpha and HCMV-gB were developed to promote de novo antiviral adaptive responses. Mice reconstituted with a human immune system (HIS) were immunized with iDCgB and challenged with HCMV, resulting into 93% protection. Immunization stimulated the expansion of functional effector memory CD8 + and CD4 + T cells recognizing gB. Machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 71 publications
3
40
0
Order By: Relevance
“…We have shown that HIS mice develop functional human memory CD4 + and CD8 + T cells and fully mature IgG + and IgA + B cells reactive against human herpes antigens. 32 , 37 , 39 We have also shown that challenge of HIS mice with EBV/B95-8 resulted in LPD (perivascular lesions with abundant tumor infiltrating lymphocyte [TILs]) and a pathology recapitulating DLBCL (large and necrotic lesions with fewer TILs). 32 A hallmark of EBV LPD progression toward DLBCL was emergence of highly activated/exhausted PD-1 + CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that HIS mice develop functional human memory CD4 + and CD8 + T cells and fully mature IgG + and IgA + B cells reactive against human herpes antigens. 32 , 37 , 39 We have also shown that challenge of HIS mice with EBV/B95-8 resulted in LPD (perivascular lesions with abundant tumor infiltrating lymphocyte [TILs]) and a pathology recapitulating DLBCL (large and necrotic lesions with fewer TILs). 32 A hallmark of EBV LPD progression toward DLBCL was emergence of highly activated/exhausted PD-1 + CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the germinal center is the primary site of B cell-T cell collaboration, antibody affinity maturation and class switching, multiple groups sought to improve LN formation and germinal center development ( 158 ). Adoptive transfer of autologous human DCs lentivirally transduced to express GM-CSF, IFNα, and human cytomegalovirus (HCMV) viral antigen enhances LN development in humanized NRG mice, and by extension promotes T cell-B cell collaboration and the production of neutralizing anti-HCMV antibodies ( 161 , 162 ). Human fetal organ co-transplantation also partially rescues secondary lymphoid organ development.…”
Section: Future Challenge #2: Adaptive Immunitymentioning
confidence: 99%
“…We have successfully used and validated the described approach for effective isolation of antigenspecific antibodies against human immunodeficiency virus 1 (HIV-1) 36 , human cytomegalovirus (HCMV) 45 , Ebola virus 34 and SARS-CoV-2 37 , as well as hepatitis C virus (HCV) and Middle East respiratory syndrome coronavirus (MERS-CoV, unpublished data). However, the pipeline is broadly applicable to a plethora of pathogens.…”
Section: Applications Of the Methodsmentioning
confidence: 99%
“…1, stage I, . We and others have successfully performed single B-cell sorting with numerous pathogen-derived surface proteins to identify pathogen-specific B cells 34,[36][37][38][43][44][45] .…”
Section: (I) Antigen-specific B-cell Isolationmentioning
confidence: 99%